KOMUNIKASI ANTAR PRIBADI ORANG TUA DENGAN ANAK KETERBELAKANGAN MENTAL - Syisva Nurwita (UNIVED PRESS, Universitas Dehasen Bengkulu, 2014)
This research is entitled Interpersonal Communication of Parents with Children who Have Mental Retardation. In this research, the researcher wants to know how communication is used by parents with mental retardation. The aim of this research is to describe the interpersonal communication that is used in communicating with mentally retarded children. This research is a descriptive qualitative study using data collection technique that uses the technique of participant observation, in-depth interviews, and documentation. The result of this study shows that the interpersonal communication of parents with children who have mental retardation is interpersonal communication through verbal and non-verbal communication. The interpersonal communication is the most appropriate communication of parents of mentally retarded children because the interpersonal communication uses multiple stages, including contacts, involvement, and familiarity. The interpersonal communication is used for children with mental retardation can complete tasks the duties of the development of a normal child of his age.Keywords: Interpersonal Communication, Parents and Children, Mental Retardation